Digital Transformation and Port Operational Risk Reduction: The Mediating Role of Integrated Information Systems - Ramadhan Hasri Harahap; Arika Palapa; Tri Cahyadi; Larsen Barasa; Marudut Bernadtua Simanjuntak (Dinasti International Journal of Education Management and Social Science, 2026)
Ports play a critical role in national logistics systems, yet operational risks remain a major challenge, particularly in developing countries where digital transformation is still evolving. This study aims to examine the effect of digital transformation on port operational risk reduction in Indonesia, with integrated information systems, operational efficiency, and operational reliability as mediating variables. A quantitative approach was employed using questionnaire data collected from 125 port employees, analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that digital transformation has a significant positive effect on integrated information systems (β = 0.853, p < 0.001). Integrated information systems significantly influence operational efficiency (β = -0.594, p < 0.001) and operational reliability (β = -0.310, p = 0.002). Furthermore, operational efficiency significantly reduces operational risk (β = 0.355, p = 0.005), while operational reliability does not have a significant effect (p = 0.065). Mediation analysis confirms that integrated information systems and operational efficiency significantly mediate the relationship between digital transformation and operational risk reduction (β = -0.180, p = 0.007), whereas the mediation through operational reliability is not supported. These findings highlight that digital transformation contributes to reducing port operational risks primarily through improving operational efficiency, providing important implications for port management and policy development.